Disclosing God in Action (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Special Issue Reprint explores British evangelicalism through the lens of its contemporary practices. It brings together fourteen original articles and an Editorial by evangelical scholars reflecting theologically on British evangelical practices. They do so critically and reflexively but also constructively, through asking how God’s action is disclosed in these practices. Together, the nineteen authors and editors address a wide range of practices, which are organised into three broad sections—worship, ministry and mission, and method. Practices include testimony, divorce, Bible engagement, rule of life, confession, youth ministry, entrepreneurship, and summer camps. The Editorial identifies common themes across the articles, such as ways in which the authors are self-critical of their own tradition; how definitions of evangelicalism are nuanced and broadened in these reflections on practice; and the surprising ways in which God is discerned as being at work. In addition, it notes how authors spoke of God in action, as well as the vehicles identified for this action. This Reprint will be an invaluable resource for all those with an interest in evangelicalism who would like to expand their understanding of the tradition through these reflective accounts of what evangelicals actually do.